Effectiveness of Chinese medicine formula Huashibaidu granule on mild COVID-19 patients: A prospective, non-randomized, controlled trial - Bowu Chen; Yan Xue; Hua Jing; Xiaodong Wang; Peimin Zhu; Weiwei Hao; Man Li; Yueqiu Gao (Integrative Medicine Research)
Background: The effectiveness and safety of herbal medicine Huashibaidu granule (HSBD) in treating mild Coronavirus Disease 2019 (COVID-19) patients infected with SARS-CoV-2 remain to be identified. We aimed to evaluate the effectiveness of HSBD in mild COVID-19 patients. Methods: A prospective, non-randomized, controlled study in mild COVID-19 patients was conducted in Shanghai, China, from April 8 to May 6, 2022. Finally, 360 mild COVID-19 patients received HSBD (orally 20 g twice daily for 7 days), and 368 patients received herbal medicine placebo (orally 20 g twice daily for 7 days). The primary endpoints were the negative conversion rate of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and the negative conversion time. Secondary endpoints included the hospitalized days and the improvement in the clinical condition. Results: The negative conversion rate of SARS-CoV-2 at 7 days posttreatment in the HSBD group was higher than that in the control group (95.28% vs. 82.61%, P < 0.001). The median negative conversion time in the HSBD group was markedly decreased by 2 days compared with the control group (3 [3–6] vs. 5 [4–7], P < 0.001). In addition, the median hospitalized day was shortened in the HSBD group by 1 day compared with the control group (6 [4–7] vs. 7 [5–9], P < 0.001). The clinical improvement rate (275/360 [76.39%]) in the HSBD group within 7 days was significantly higher than that (203/368 [55.16%]) in the control group (P < 0.001). The improvement of symptom scores in the HSBD group was higher than that in the control group (2 [1–4] vs. 1 [1–2], P < 0.001). No severe adverse events occurred. Conclusions: Our study suggested that HSBD effectively increased the negative conversion rate of SARS-CoV-2 and shortened the negative conversion time and hospitalized days in mild COVID-19 patients. Clinical trial registration: The trial was registered at Chinese Clinical Trial Registry, ChiCTR2200058668.